Bacterial resistance to indiscriminate use of azithromycin versus Covid-19: an integrative review (Research, Society and Development, 2022)
Recently a disease caused by a new corona virus, sars-cov2, was described as Covid-19, and it spread, getting a pandemic character, viral spread and consequent increase in the number of deaths worldwide, there was a Growing rise in the dissemination of prophylactic news, there was an increase in the curve of self-medication by individuals, in large part, influenced by false news made available on social media and in debates without scientific basis. In this sense, a drug that stands out is Azithromycin, an antibiotic of the azalide type, which was widely prescribed and used on a large scale by the general population. By using Azithromycin, due to its immunomodulating effect in a pathology that is essentially viral, it opens the door to an increase in bacterial resistance to this medication and its drug class. It is plausible to say that the indiscriminate use of this antibiotic, regardless of its intended function, increases the possibility of selecting resistant bacteria. Objective: Therefore, the objective was to describe bacterial resistance due to the indiscriminate use of Azithromycin compared to Covid-19. Material and Method: This was an integrative literature review from the LILACS, PUBMED/MEDELINE and SCIELO databases, between 2019 and 2021. 75 articles were identified, 10 of which were used in the preparation of the work. Results show that self-medication during this pandemic period, emphasizing the indiscriminate use of Azithromycin, in addition to emphasizing the factors that contribute to this practice, which contribute to the increase in bacterial resistance. Factors such as errors in medical indications, self-medication by the population and an ineffective inspection of the sale of antimicrobials, in pharmacies and drugstores, where these drugs are concentrated, contribute to bacterial multi-resistance. Conclusion: It is necessary to guide and clarify, both health professionals and the population, about bacterial resistance, as well as the correct and effective indication and use of antibiotics against infectious diseases.